The Study of Power Relations in Sam Shepard’s True West - Qassim Ali, Youssra (International Journal of Psychosocial Rehabilitation, 2020)
The current research intends to have a critical investigation of Sam Shepard’s True West in terms of Foucauldian concepts of power and knowledge. It will be stated that Shepard’s plays would portray a world in which there is a lack of communication between characters. What is going to be found verifies the intricate relationship between these characters. According to Foucault, this paper is going to conclude that individuals are enforced by society, and accordingly, the society changes their dreams and limits their ability to express themselves. Likewise, in True West in the relationship between Lee and Austin, power is the most important feature. In fact, the characters are an effect of power.